Visualisation software for home automation bus systems - Kocatepe, Oğuzhan (My University, 2003)
BUS TABANLI EV OTOMASYON SİSTEMLERİ İÇİN GÖRÜNTÜLEME YAZILIMI Bu tezimde bir ev otomasyon sistemine ulaşmak için bir orta kademe Java yazılımı tasarlayıp, bu yazılım aracılığıyla wap veya http protokolünden gelen istekleri ev ortamındaki çeşitli cihazları RS232 veya TCP/ IP soket bağlantısıyla bağlayan bir bus sistemine aktaracağım. Tezin ana odak noktası applet tarzında yazılarak bir grafik arabirim görevi görecek olan Java orta kademe dağıtık sistem birimidir. Tüm sistemde modern ev elektronik cihazlarının yanısıra ticari binalar da hedeflenmiştir. Bus sisteminin standardizasyonu değişik üreticilerle birlikte çalışma imkanı tanımıştır. Diğer yandan Java teknolojisi ve esnek altyapısı, platform bağımsız uygulamaların yazılmasına ve kullanılmasına izin vermiştir. Benim tasarlayacağım sistemde bahsettiğim Java arayüz görüntüleme yazılımı ile wap veya http protokolü ile ev elektronik bus sistemlerini bir araya getirmem mümkün olacaktır.

VISUALISATION SOFTWARE FOR HOME AUTOMATION BUS SYSTEMS This thesis describes an architecture that enables end-users to access to a home automation system through a middle-tier Java application, which processes the requests and forwards the commands to a bus system that connects several home devices, communicating through RS232 or TCP/ IP socket communication. The Java Agent is the actual interface which is very open and flexible. The main focus of the thesis is the applet style pieces of Java code that implements logical behaviour or graphical user interfaces for the bus system. This distributed architecture can be used to accept incoming messages through http or wap protocols. The whole system is aimed to be successful to facilitate modern electrical installations for homes as well as commercial buildings. The standardization of the bus system allows interoperability between different manufacturers. On the other hand, the Java technology and its unique and flexible architecture provide platform independent development and deployment of Java applications. The system that I'll try to implement will bring together the wap telecommunication or http protocol with my visualisation software which is actually a Java interface and the electronical bus system.
Keywords: Bilgisayar; bilgisayar bilimi; Genel Konular; Veri işleme; Yazılım Sistemleri